Activation of CAMK2 by pseudokinase PEAK1 represents a targetable pathway in triple negative breast cancer - Yang, Xue; Ma, Xiuquan; Zhao, Tianyue; Croucher, David R.; Nguyen, Elizabeth V.; Clark, Kimberley C.; Hu, Changyuan; Latham, Sharissa L.; Bayly-Jones, Charles; Nguyen, Bao V.; Budnar, Srikanth; Shin, Sung-Young; et al. (Nature communications, 2025)
The PEAK family of pseudokinases, comprising PEAK1-3, play oncogenic roles in several poor prognosis human cancers, including triple negative breast cancer (TNBC). However, therapeutic targeting of pseudokinases is challenging due to their lack of catalytic activity. To address this, we screen for PEAK1 effectors and identify calcium/calmodulin-dependent protein kinase 2 (CAMK2)D and CAMK2G. PEAK1 promotes CAMK2 activation in TNBC cells via PLCγ1/Ca 2+ signalling and direct binding to CAMK2. In turn, CAMK2 phosphorylates PEAK1 to enhance association with PEAK2, which is critical for PEAK1 oncogenic signalling. To achieve pharmacologic targeting of PEAK1/CAMK2, we repurpose RA306, a second generation CAMK2 inhibitor. RA306 inhibits PEAK1-enhanced migration and invasion of TNBC cells in vitro and significantly attenuates TNBC xenograft growth and metastasis in a manner mirrored by PEAK1 ablation. Overall, these studies establish PEAK1 as a critical cell signalling nexus that integrates Ca 2+ and tyrosine kinase signals and identify CAMK2 as a therapeutically ‘actionable’ target downstream of PEAK1. The PEAK family of pseudokinases is known to play oncogenic roles in poor-prognosis triple negative breast cancer (TNBC). Here this group identifies the role of calcium/calmodulin-dependent protein kinase 2 (CAMK2) in targeting downstream of PEAK1 thereby utilizing RA306 (CAMK2 inhibitor) to effectively attenuate TNBC xenograft growth and block metastasis as well.